Kvantni simulatorji - Pelaič, Jaka (Matrika, 2019)
The aim of this article is to provide an overview of the field of quantum simulation. Its historical and practial motivations are first given, followed by a short introduction to composite quantum systems and a basic outline of quantum computation. The two major paradigms of quantum simulation, id est digital (DQS) and analogue (AQS), are described. The efficiency of such simulators and the fundamental problem of decoherence which plagues all practical realisations are then commented on; some examples of such realisations are given along with their possible advantages and shortcomings. The seminar concludes with future expectations for practical implementations of this technology.
Keywords: kvantna mehanika; kvantna simulacija; kvantno računalništvo; quantum computers; quantum mechanics; quantum simulation